Topography-Guided Transepithelial Accelerated Corneal Collagen Cross-Linking for Low Refractive Error Correction in Keratoconus Treatment: A Pilot Study - Sun, Ling; Zhang, Xiaoyu; Tian, Mi; Shen, Yang; Zhao, Jing; Zhou, Xingtao (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To investigate the safety and efficacy of topography-guided transepithelial accelerated corneal collagen cross-linking for low refractive error correction in patients with keratoconus. Methods: This was a prospective self-controlled study. Eighteen patients (18 eyes) were enrolled and assessed at 6 visits (pre-operation, 1 w, 1 month, 3 months, 6 months, and 1 year postoperatively). The examination at every visit included analysis of uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), corneal topography, and corneal endothelial cell counts. Data are expressed as mean ± standard deviation (SD). The P-value was determined using repeated-measures analysis of variance. Results: No complications occurred in any eye during 1 year follow-up period. At each visit after the operation, the corneal K values and spherical equivalent (SE) were reduced, while the visual acuity values were increased compared with those preoperatively, although these results were not statistically significant(P>0.05). UCVA of nearly 1/3 of the patients was enhanced by at least 3 lines at each follow-up visit. During the whole follow-up, corneal endothelial cell counts were stable (P>0.05). Regarding topography, part of the corneal cone was flattened after the operation. Conclusion:Topography-guided transepithelial-accelerated corneal collagen cross-linking is safe and may correct low refractive error in keratoconus treatment. Further studies and improvements are required in this regard.